Eye of the tiger sign in neurodegeneration with brain iron accumulation: a case report - Mondal, Sumantro; Dey, Debasish; Ete, Tony; Sinha, Debanjali; Nag, Arijit; Chakraborty, Atanu; Prasad, Amod (International Journal of Research in Medical Sciences, 2017)
Neurodegeneration with brain iron accumulation (NBIA) is a rare autosomal recessive disorder characterized by abnormal accumulation of ferritin in globus pallidus of brain. Magnetic resonance imaging (MRI) of brain demonstrates a characteristic ‘eye-of-the-tiger’ sign. We describe a case of NBIA in a child with classical clinical and MRI of brain features.